2021
DOI: 10.1126/sciadv.abf1973
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion dynamics in the neocortex determine the start of migration and the post-migratory orientation of neurons

Abstract: The neocortex is stereotypically organized into layers of excitatory neurons arranged in a precise parallel orientation. Here we show that dynamic adhesion both preceding and following radial migration is essential for this organization. Neuronal adhesion is regulated by the Mowat-Wilson syndrome-associated transcription factor Zeb2 (Sip1/Zfhx1b) through direct repression of independent adhesion pathways controlled by Neuropilin-1 (Nrp1) and Cadherin-6 (Cdh6). We reveal that to initiate radial migration, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…For example, C3G-Rap1 mediated inside-out activation of α5β1 integrin is required for neuronal migration (Sekine et al, 2012;Shah et al, 2016). However, a more recent study has indicated that that Zeb2mediated downregulation of β1 integrin surface expression may enable timely migration from the subventricular zone (Epifanova et al, 2021). Similarly, elevated expression of β1 integrin and FAK in glia due to deletion of MARVELD1, a novel nuclear protein, also caused aberrant neuronal migration (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, C3G-Rap1 mediated inside-out activation of α5β1 integrin is required for neuronal migration (Sekine et al, 2012;Shah et al, 2016). However, a more recent study has indicated that that Zeb2mediated downregulation of β1 integrin surface expression may enable timely migration from the subventricular zone (Epifanova et al, 2021). Similarly, elevated expression of β1 integrin and FAK in glia due to deletion of MARVELD1, a novel nuclear protein, also caused aberrant neuronal migration (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%